Knowledge and attitudes of pharmacists regarding oral health care and oral hygiene products in Chennai city - Priya Shanmuga; Madan Kumar P; Ramachandran S (Wolters Kluwer Medknow Publications, 2008)
Objectives : This study was done to find out the knowledge and attitudes of pharmacists regarding oral health care and oral hygiene products in Chennai city. Materials and Methods : A cross-sectional survey among a sample of the pharmacists in Chennai city was done and data regarding their knowledge and attitudes towards oral health care and oral hygiene products were obtained using a closed-ended questionnaire. Results: Among the 60 pharmacies approached, 50 pharmacists participated in the study and completed the questionnaire. Though 48% of the participants gave a positive answer when asked whether they had met the dentist practicing close to their pharmacies, the frequency with which they met the dentist ranged from once a week (24%) to once a month (28%). Most of the pharmacists stocked oral health-related products, which comprised 15-25% of their total stock. Of these products toothpaste was the most common (62%), followed by mouth rinses (12%). Toothache or painful teeth was the most common dental problem (78%) for which patients approached the pharmacists for advice. With regard to the advice given, 38.5% of the pharmacists asked the patient to consult a nearby dentist after dispensing medications, while 22.4% of the pharmacists dispensed antibiotics and painkillers without any referral. Seventy percent of the pharmacists expressed interest in giving oral health care advice to patients. However, many of them (38%) felt that lack of proper knowledge is a barrier to providing oral health care advice. Conclusion : It is clear from the present study that pharmacists are presently an underutilized resource, and there is a definitive need to improve their training and access to information on available dental services.